Avaliação do desempenho térmico em dois aviários de frango de corte dark house com diferentes tipos de cobertura - Silva, Renata Galvan Rutz da (2020)
In view of the worldwide importance of broiler poultry, the manner and conditions in which the birds are developed, especially regarding the environment, is of interest to producers, researchers, consumers and other people related to the sector. Thus, the aforementioned work aims to evaluate the thermal performance, through the comfort parameters, of two broiler chicken houses, dark house model, called AV1 and AV2, with different types of coverings and located in the city of Ubiratã, in the western region of the State of Paraná, Brazil. The AV1 aviary is characterized by a dimension of 15x150 meters, coverage with ceramic clay tile and black canvas lining and houses about 31.500 birds, while the AV2 aviary is characterized by a dimensioning of 16x150 meters, cover with trapezoidal aluzinc tile and black canvas lining and houses approximately 34.000 birds. The research followed a complete cycle of housing in three stages of development of the birds, which are the initial, the growth and finishing. The data acquisition system on each collection date occurred in two different periods, morning and afternoon, and for the survey of temperature and relative humidity, indoor and outdoor, a thermo-hygrometer, THDL - 400 Environment Meter, was used Instrutherm brand, and a thermographic camera was used to record the thermographs in order to identify the birds' surface temperature. After organizing the information obtained, comparative analyzes were carried out using the Tukey Test, at the level of 5%, in order to identify whether there is a significant difference between the treatments, namely the av1 aviary coverage and the av2 aviary coverage. During the collection weeks, the lowest internal temperature recorded was 30.92 ºC, in the sixth week in the morning, in the aviary AV1. While the highest internal temperature was 36.71 ºC, also in the sixth week in the morning, however, in the AV2 aviary. As for the internal relative humidity, the lowest and highest value found was 23.53% and 70.06% for the sixth week of collection in the morning and afternoon, respectively, in the AV1 aviary. Regarding the surface temperature or lowest result was 37.78 ºC, in the sixth week in the morning, and a maximum of 45.23 ºC, in the first week in the afternoon, both in the AV2 aviary. Finally, it can be concluded that the aviary with a ceramic clay tile coverage presented thermal comfort conditions closer to the values considered ideal by the literature.